URGENSI KOMUNIKASI DALAM MENUNJANG EFEKTIVITAS PENYELENGGARAAN PELAYANAN PUBLIK - Andi Wahyudi (Jurnal Borneo Administrator, 2010)
The objectives of this study are (1) to search the effect of communication  in public service process; (2) to search communication models which effectively support to public service delivery. This study uses descriptive analysis method and qualitative approach. The data is based on the result of public complaint survey to AW. Sjahranie Hospital’s service in Samarinda and the researcher’s observation during the workshop on public complaint management. The result of this study that there are still many problems in communication implementation between hospital’s employee and public, because the service provider often do not give information clearly both by talking, written or picture/signs. That’s way the communication in this hospital has not effective nor interactive yet. The lack of communication tends to produce misunderstanding excess in delivering public service. Therefore, good communication between civil servant and public is urgent in this hospital to create the same understanding and reduce wrong perception. The effective communication can be built through interpersonel communication, and use media just alike an interesting writting board, pictures or signs that are easy to see.  Keywords: communication, effectivity, public service